DEVELOPMENT OF QUALITATIVE PHARMACOGNOSTIC AND HIGH-PERFORMANCE THIN-LAYER CHROMATOGRAPHIC FINGERPRINTING OF MORPHOLOGICAL SIMILAR SPECIES OF GENUS FICUS - Singh, Amandeep; Mukhtar, Hayat Mohammad; Satija, Saurabh; Mehta, Meenu (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Ficus deltoidea (FD) and Ficus benjamina (FB), popularly known as jack tree/mas cotekâ€ and pimpri/java fig,â€ respectively, in India and are used in folk medicine to treat the wound, ulcers, diabetes, microbial infections, and inflammatory disorders. Such therapeutic claims have also been justified in the literature by their rich chemical diversity. Both the plant species are morphologically similar and used unauthentically as the traditional medicinal product. Although these plants are sold in the local market by a traditional medicinal healer, we did not find any authenticated data on its quality. Methods: In the present study, quality standards of both the plant drugs have been developed and compared by performing morphological, microscopical, physicochemical, phytochemical, and high-performance thin-layer chromatographic (HPTLC) analysis. using CAMAG Linomat 5 instrument (Kindly delete the bold matter). Results: It was revealed that both the plant species have similar pharmacognostic features with some differences in type of stomata, presence of marked midrib, arrangement of the cell, cell structures, and meristele. HPTLC data revealed that the primary component in FD leaves (FDL) and FB leaves (FBL) extracts was found at Rf 0.67 and 0.37 with the respective peak area of 35.61% and 34.71%. The peaks at Rf 0.17 and 0.27 can be appeared as the chemical marker to highlight the quality of FDL, whereas peaks at Rf 0.87 and 0.95 can be considered to identify and chemically standardize the FBL. Conclusion: This study highlighted essential characters which contribute to the standardization, identification, and authentication of plant drugs.